ANALYSIS OF THE IMPLEMENTATION OF GOOD GOVERNANCE PRINCIPLES ON PUBLIC SERVICE QUALITY - Laila Qadriyani Malikin Rumakat (PT. Radja Intercontinental Publishing, 2026)
This study in the field of Public Administration is motivated by the persistently low quality of public services, reflecting weak implementation of Good Governance, particularly in terms of transparency and responsiveness. The objective of this study is to analyze the effect of good governance principles on the quality of public services. A quantitative approach with an explanatory design was employed, involving 120 respondents who were public service users in Manokwari Regency, selected through accidental sampling. Data were collected using a Likert-scale questionnaire and analyzed using linear regression. The results indicate that the implementation of good governance has a positive and significant effect on public service quality, with responsiveness emerging as the most dominant factor directly enhancing user satisfaction and perceived service quality. This finding highlights a novel contribution, demonstrating that strengthening responsiveness based on local needs is more effective than formal administrative approaches. The study concludes that the adaptive optimization of good governance principles is a key strategy for improving public service quality.Good Governance